2023
DOI: 10.1108/md-01-2022-0007
|View full text |Cite
|
Sign up to set email alerts
|

Does board diversity reduce the likelihood of financial distress in the presence of a powerful Chinese CEO?

Abstract: PurposeThis paper empirically investigates the impact of board diversity in terms of demographic and cognitive dimensions on financial distress likelihood in an emerging Chinese market to explore whether the Chief Executive Officers' (CEOs) power moderates the relationship between board diversity and the probability of financial distress.Design/methodology/approachTo test the hypothesized relationships, demographic diversity through gender, age and nationality, and cognitive diversity through education, expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…It shows that cash resources from tax planning are managed in distinctive ways in each life cycle stage, thereby having a varied impact on the likelihood of default. Our study sheds light on the underexplored non-VRIO cash resources, and highlights the potential linkages between the agency theory and RBV (Luu, 2023;Ali et al, 2023).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It shows that cash resources from tax planning are managed in distinctive ways in each life cycle stage, thereby having a varied impact on the likelihood of default. Our study sheds light on the underexplored non-VRIO cash resources, and highlights the potential linkages between the agency theory and RBV (Luu, 2023;Ali et al, 2023).…”
Section: Discussionmentioning
confidence: 70%
“…We use another measure of the dependent variable and replicate the analysis. We use the Altman Z-score (Altman, 1968;Ali et al, 2023) [9] as an alternative to financial default. The results remained consistent with our main findings (untabulated).…”
Section: Robustness and Endogeneity Checksmentioning
confidence: 99%
“…It has been shown that having a diverse board of directors can help businesses make better decisions, be more innovative, and perform better financially. Research on the function of diverse boards in developing nations is necessary, as the majority of the material currently in publication focuses on industrialized nations [28], [29], [30]. This research gap necessitates studies that are appropriate for the setting of emerging nations, accounting for variations in culture, institutions, and regulations.…”
Section: Board Diversity In Startupsmentioning
confidence: 99%